Works by Pyotr Ilyich Tchaikovsky in the USARB Scientific Library collection (Confluenţe Bibliologice, 2020)
The author of this article writes about the exhibition dedicated to the great Russian composer Pyotr Ilyich Tchaikovsky, on the occasion of the 180th anniversary of his birth. The USARB Scientiﬁc Library collection includes: 165 complete works and works in diﬀerent editions, 32 audiovisual documents and 14 electronic documents, 106 critical monographs in Romanian, Russian and foreign languages, articles from periodicals, accompanied by the bibliography of traditional and electronic resources.
Keywords: Russian classical composers; Piotr Ilyich Tchaikovsky (1840–1893); collection of the USARB Scientiﬁc Library